Rough sets methods in feature reduction and classification - Świniarski, Roman W. (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents an application of rough sets and statistical methods to feature reduction and pattern recognition. The presented description of rough sets theory emphasizes the role of rough sets reducts in feature selection and data reduction in pattern recognition. The overview of methods of feature selection emphasizes feature selection criteria, including rough set-based methods.
Keywords: rough sets; feature selection; classification